New agents with potential leishmanicidal activity identified by virtual screening of chemical databases: New agents with potential leishmanicidal activity - Juan Rebollo; Jesús Olivero-Verbel; Niradiz Reyes (Salud UIS, 2013)
Introduction and Objectives: Leishmaniosis, a disease caused by a protozoan parasite, remains a serious public health problem threatening about 350 million people around the world, of which 12 million are believed to be currently infected (WHO 2010). To date, there are no vaccines against the species of parasites and the treatment is based only on chemotherapy with toxic-, expensive- and inefficient- drugs. There is an urgent need for better drugs against Leishmania, the etiological agent of the disease. The main anti-leishmanial drug used in Colombia is meglumineantimoniate [chemical name according to the International Union of Pure and Applied Chemistry (IUPAC): Hydroxy-dioxostiborane; (2R,3R,4R,5S)- 6-methylaminohexane-1,2,3,4,5-pentol, (C7H17NO5)], which is not efficient in the treatment of infections caused by Leishmania braziliensis, the most prevalent specie in the Caribbean coast of Colombia. Methods: We performed an in silico virtual screening of several datasets including ChemBridge and Pubchem. We virtually screened a total of 28.755 compounds against a 3D model of 6-phosphoglucono -lactonase (6-PGL) from Leishmania braziliensis to identify novel inhibitors.Molecular docking of databases was performed using the software Sybyl 8.0 and AutoDockVina. Results: The initial virtual screening using a structure-based method identified 10 compounds, which were later tested with AutodockVina and classified according to their docking scores. Conclusions: These novel and potential inhibitors constitute new drug candidates that must be biologically tested to define their value as an alternative chemotherapeutic agent in the treatment of these protozoan infections. Salud UIS 2013; 45 (1): 33-40